2010
DOI: 10.1002/ar.21103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Morphology of the Chick Heart Visualized by MALDI Imaging Mass Spectrometry

Abstract: Utilization of MALDI-MS (matrix-assisted laser desorption/ionization mass spectrometry) for tissue imaging is a relatively new proteomic technique that simultaneously maps the spatial distribution of multiple proteins directly within a single frozen tissue section. Here we report the development of a methodology to apply MALDI tissue imaging to chick heart tissue sections acquired from fixed and paraffin-embedded samples. This protocol produces molecular images that can be related to the high quality histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Perhaps not unexpectedly, the most abundant ions observed below m/z 1500 in the MALDI IMS experiment of tissues such as brain (6), kidney (7), liver (8), eye (9), and blood vessels (10) were derived from those lipids that make up the various membranes of the living cell (phospholipids and sphingolipids) as well as lipid storage vesicles found in abundance in certain cell types. The most abundant positive ions typically observed are derived from a single class of lipid called phosphatidylcholine (PC), but within that class are numerous molecular species that differ from each other by fatty acyl group esterification to the glycerophosphocholine backbone.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps not unexpectedly, the most abundant ions observed below m/z 1500 in the MALDI IMS experiment of tissues such as brain (6), kidney (7), liver (8), eye (9), and blood vessels (10) were derived from those lipids that make up the various membranes of the living cell (phospholipids and sphingolipids) as well as lipid storage vesicles found in abundance in certain cell types. The most abundant positive ions typically observed are derived from a single class of lipid called phosphatidylcholine (PC), but within that class are numerous molecular species that differ from each other by fatty acyl group esterification to the glycerophosphocholine backbone.…”
Section: Introductionmentioning
confidence: 99%
“…The distributions obtained for ubiquitin, calcyclin, calgizzarin, and transthyretin were found to be similar to their respective mrnA expressions by in situ hybridization experiments, thus validating the approach [46]. grey et al [47] reported on the visualization of the molecular morphology of the chick heart using IMS. Tissue sections from term chicks were obtained and coated with either chcA, DhB, or SA.…”
Section: Anatomy and Developmentmentioning
confidence: 58%
“…One fixation approach that has worked well for obtaining signal from cardiac tissue is fixation by acidified ethanol prior to sectioning [26]. Fresh cardiac tissue is incubated overnight in a cold, acidic solution of ethanol.…”
Section: Sample Preparation For Imaging Intact Proteins From Cardimentioning
confidence: 99%
“…Evaluation of chicken heart treated in this manner showed that heart tissue has significant protein gradients throughout the heart with unique proteins found in ventricles, vessels or heart valves. This was one of the first illustrations of the use of MALDI IMS to detect proteomic content from a cross section of heart tissue while retaining localization to histological features [26]. …”
Section: Sample Preparation For Imaging Intact Proteins From Cardimentioning
confidence: 99%